Entrepreneurship Development by Small & Medium Enterprises in Sylhet: Problems and Prospects - Khanom, Tahmina (American Journal of Trade and Policy, 2015)
This paper analyses the entrepreneurship practices in the small and medium enterprises in Sylhet. In this study forty- five samples have been surveyed under nine different categories of Small and Medium Enterprises (SMEs) operating in Sylhet. The categories were –retailing, tailoring, boutique shop, flowers shop, pharmacy, restaurant, mobile servicing shop, fast food shop and phone and fax shop. Both structured and unstructured questions were used in the questionnaire to collect the data and also some published materials are studied to find out the business constraints and potentiality of SMEs in this region. This study reveals that SMEs are contributing as engines of economic growth to a large extent in this region. The finding of the study reveals that, besides possessing a high potentiality, SMEs are facing a lot of problems like inadequate capital, raw materials collection, high cost of operating, financing and marketing, insufficient support facilities, unstable political situation, etc. An attempt has been made to identify major obstacles and potentially of doing business by using SMEs and recommend some policy measures for overcoming the constraints.